'Jewish Enough for You?': Howard Jacobson on Screen. Issue 2 (1st September 2022) - Herman, David
Abstract: Howard Jacobson is one of the leading Anglo-Jewish writers of the past forty years. He has received considerable acclaim but articles about Jacobson have rarely featured his career as a broadcaster, on British television and radio. Since the 1980s he has regularly appeared as a subject of TV documentaries, including Arena (BBC2) and The South Bank Show (ITV), a presenter of individual programmes such as Sorry, Judas and The South Bank Show: Why the Novel Matters to Roots Schmoots and Seriously Funny and a number of discussion programmes, including Start the Week (Radio 4), The Sundays (Channel 4) and The Late Show (BBC2).